Calcium signaling mediates proliferation of the precursor cells that give rise to the ciliated left-right organizer in the zebrafish embryo - Abdel-Razek, Osama; Marzouk, Amanda; MacKinnon, Madison; Guy, Edward T.; Pohar, Sonny A.; Zhushma, Emily; Liu, Junjie; Sia, Isabel; Gokey, Jason J.; Tay, Hwee Goon; Amack, Jeffrey D. (Frontiers in Molecular Biosciences, 2023)
Several of our internal organs, including heart, lungs, stomach, and spleen, develop asymmetrically along the left-right (LR) body axis. Errors in establishing LR asymmetry, or laterality, of internal organs during early embryonic development can result in birth defects. In several vertebrates-including humans, mice, frogs, and fishcilia play a central role in establishing organ laterality. Motile cilia in a transient embryonic structure called the 'left-right organizer' (LRO) generate a directional fluid flow that has been proposed to be detected by mechanosensory cilia to trigger asymmetric signaling pathways that orient the LR axis. However, the mechanisms that control the form and function of the ciliated LRO remain poorly understood. In the zebrafish embryo, precursor cells called dorsal forerunner cells (DFCs) develop into a transient ciliated structure called Kupffer's vesicle (KV) that functions as the LRO. DFCs can be visualized and tracked in the embryo, thereby providing an opportunity to investigate mechanisms that control LRO development. Previous work revealed that proliferation of DFCs via mitosis is a critical step for developing a functional KV. Here, we conducted a targeted pharmacological screen to identify mechanisms that control DFC proliferation. Small molecule inhibitors of the sarcoplasmic/endoplasmic reticulum Ca 2+ -ATPase (SERCA) were found to reduce DFC mitosis. The SERCA pump is involved in regulating intracellular calcium ion (Ca 2+ ) concentration. To visualize Ca 2+ in living embryos, we generated transgenic zebrafish using the fluorescent Ca 2+ biosensor GCaMP6f. Live imaging identified dynamic cytoplasmic Ca 2+ transients ('flux') that occur unambiguously in DFCs. In addition, we report Ca 2+ flux events that occur in the nucleus of DFCs. Nuclear Ca 2+ flux occurred in DFCs that were about to undergo mitosis. We find that SERCA inhibitor treatments during DFC proliferation stages alters Ca 2+ dynamics, reduces the number of ciliated cells in KV, and alters embryo laterality. Mechanistically, SERCA inhibitor treatments eliminated both cytoplasmic and nuclear Ca 2+ flux events, and reduced progression of DFCs through the S/G2 phases of the cell cycle. These results identify SERCA-mediated Ca 2+ signaling as a mitotic regulator of the precursor cells that give rise to the ciliated LRO.